Molecular mechanisms for the prevention and promoting the recovery from ischemic stroke by nutraceutical laminarin: A comparative transcriptomic approach - Luo, Jiefeng; Chen, Dingzhi; Qin, Biyun; Kong, Deyan (Frontiers in Nutrition, 2022)
Stroke is the second leading cause of death and a major cause of disability worldwide. Ischemic stroke caused by atherosclerosis accounts for approximately 87% of all stroke cases. Ischemic stroke is a preventable disease; therefore, a better understanding of the molecular mechanisms underlying its pathogenesis and recovery processes could provide therapeutic targets for drug development and reduce the associated mortality rate. Laminarin, a polysaccharide, is a nutraceutical that can be found in brown algae. Accumulating evidence suggests that laminarin could reduce the detrimental effects of neuroinflammation on brain damage after stroke. However, the molecular mechanism underlying its beneficial effects remains largely unknown. In the present study, we used a middle cerebral artery occlusion (MCAO) rat model and applied comparative transcriptomics to investigate the molecular targets and pathways involved in the beneficial effects of laminarin on ischemic stroke. Our results show the involvement of laminarin targets in biological processes related to blood circulation, oxygen supply, and anti-inflammatory responses in the normal brain. More importantly, laminarin treatment attenuated brain damage and neurodeficits caused by ischemic stroke. These beneficial effects are controlled by biological processes related to blood vessel development and brain cell death through the regulation of canonical pathways. Our study, for the first time, delineated the molecular mechanisms underlying the beneficial effects of laminarin on ischemic stroke prevention and recovery and provides novel therapeutic targets for drug development against ischemic stroke.